SGLT 2 Inhibitors: Mechanisms, Clinical Applications, and Future Directions - Çakmak, Abdülkadir (International Journal of Computational and Experimental Science and Engineering, 2024)
Due to the progressive and painful nature of type 2 diabetes (T2D), treatment may require periodic evaluation of patients, intensifying glucose-lowering therapy when glycaemic targets are not achieved and testing new methods. Among the newer classes of glucose-lowering drugs, sodium-glucose cotransporter 2 inhibitors (SGLT2is), which increase urinary glucose excretion to reduce hyperglycaemia, have made an impressive entry into the T2D treatment arsenal. Given their unique insulin-independent mode of action and favourable efficacy-adverse effect profiles, and their apparent benefits on cardiovascular-renal outcomes in intermediate-high-risk T2D patients, which have led to the updating of guidelines and product monographs, the role of this drug class in multidrug regimens is promising. However, despite much speculation based on pharmacokinetic and pharmacodynamic properties, physiological rationale and potential synergism, the glycaemic and pleiotropic effects of these agents when combined with other classes of glucose-lowering drugs remain largely under-researched. Therefore, this review discusses the mechanisms, clinical applications and future therapeutic role of SGLT2 inhibitors with a review of the literature.